Effect of Posterior Tibial Nerve Stimulation on Overactive Bladder Among Multigravida Mothers - Parameshwari, .; Kumaresan, Abathsagayam; Vijay, Chandhini; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Vinodhkumar, Ramalingam; Buvanesh, Annadurai (INTI International University, 2023)
Background and objective:To evaluate the efficiency of posterior tibial nerve stimulation on multigravida mother’s overactive bladder.Urine urgency, excessive urination, and urinary urgency in nights are the hallmarks of overactive bladder syndrome (OAB), a urological condition that may or may not be followed by urinary incontinence (UI).This is a chronic disease that affects millions of women worldwide, with the risk of death increasing as they become older.Despite the fact that there is no immediate danger to life, it significantly impacts the health. In multigravida mothers, the lower urinary system, which includes the bladder and urethra, functions as a single functional unit. A technique for symptom evaluation called theoveractive bladder symptom score OABSS aims to sum up all OAB symptoms into a single score. Method: This pilot study was conducted at Saveetha medical college and hospital. Using inclusion and exclusion criteria samples were selected for the period of 4 weeks. Before and after the conclusion of treatment, the patients' OABSS were evaluated. Then the patients were treated with transcutaneous electric nerve stimulation for 4 weeks. Results: Comparing pre-test and post-test values in the experiment group revealed a statistically significant difference, according to statistical analysis of quantitative data, (P<0.0001) in OAB symptom score was recorded in multigravida women. Conclusion: This study concludes that posterior tibial nerve stimulation is effective in overactive bladder among multigravida mothers measured using OAB symptom score